Personality and location-based social networks. (May 2015) - Chorley, Martin J.; Whitaker, Roger M.; Allen, Stuart M.
Highlights: We investigate personality and use of location based social networks. We examine the five-factor personality model against places that users check-in at. Conscientiousness positively correlates with the number of venues visited. Openness positively correlates with check-ins at both sociable and popular venues. Neuroticism negatively correlates with the number of sociable venues visited. Abstract: Location-based social networks (LBSNs) are a recent phenomenon for sharing a presence at everyday locations with others and have the potential to give new insights into human behaviour. To date, due to barriers in data collection, there has been little research into how our personality relates to the categories of place that we visit. Using the Foursquare LBSN, we have released a web-based participatory application that examines the personality characteristics and checkin behaviour of volunteer Foursquare users. Over a four-month period, we examine the behaviour and the "Big Five" personality traits of 174 anonymous users who had collectively checked in 487, 396 times at 119, 746 venues. Significant correlations are found for Conscientiousness, Openness and Neuroticism. In contrast to some previous findings about online social networks, Conscientiousness is positively correlated with LBSN usage. Openness correlates mainly with location-based variables (average distance between venues visited, venue popularity, number of checkins at sociable venues). For Neuroticism, further negative correlations are found (number of venues visited, number of sociable venues visited). No correlations are found for the other personality traits, which is surprising for Extroversion. The study concludes that personality traits help to explain individual differences in LBSN usage and the type of places visited.